Assessment of SDG 3 to achieve health objectives in South African context - Vyas-Doorgapersad, Prof Shikha (Journal of Ecohumanism, 2025)
Every person has a right to live in a healthy environment, have access to healthy food and medications. Non-realisation of such health benefits may lead to negative impact on people’s overall wellness. This is the aim of the article to examine the status quo of sustainable development goal (SDG) 3 (focus) in the South African context (locus). The article uses a qualitative research approach to compile information that is already published. The secondary data is gathered using document review and further assessed through document analysis. The findings explore that there are various factors that may cause effective achievement of health objectives in the country. Some of them could be linked to poverty and unemployment whereby people cannot afford medical services; geography whereby community members living in marginalised areas struggle to get access to hospitals and doctors; other factors could be political, technological and infrastructure-related, all requiring strategic decisions and policies to improve the health context. Based on the findings, the article offers suggestions for consideration by policymakers, strategic decision-makers and stakeholders to be participatory, aware and diligent in health and wellness decisions and programmes to receive the desired benefits.